Business and IT Strategic Alignment: An Assessment of A Commercial Approach - Jaworski, Paul (2007)
The principal aim of this management project was to provide answers to the question to what extent does academic theory influence / support the corporate approach to strategic alignment, as expressed in published strategy documents?